Electrical properties of metal-ferroelectric-insulator-semiconductor structure using BaxSr1-xTiO3 for ferroelectric-gate field effect transistor - Saif, Ala’eddin A.; Poopalan, Prabakaran, Prof. Madya (Elsevier Ltd., 2011)
Link to publisher's homepage at http://www.elsevier.com/